Interaction of Religions and Expression of National Identity of Immigrants in Works by Vietnamese Diasporic Writers Living in France - Nguyen Thi Nhu Trang, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Vietnamese writers living in France such as Linda Le or Thuan have integrated into the stream of contemporary European literature. They delved into the lives and the fate of Vietnamese refugees who had migrated to France, of “Étranges étrangers” (as called by Linda Le), of those who did not belong anywhere, of people with no roots. Thus, Linda Le and Thuan reflected the ambivalences in the national identities of immigrants. One of the main factors that lead to these ambivalences in the national identity of immigrants is religious interaction. Vietnamese religions (indigenous religions and the three religions Taoism, Buddhism, and Confucianism) have deep traces in the minds of Vietnamese people, influencing their thoughts and behavior, giving them a perception of the world and the way of life. Despite being surrounded by Christian culture, they never considered themselves to be purely French. They also did not identify themselves as immigrant minorities. They can be called “Étranges étrangers”, those that live between two religions and two cultures. This paper examines the relationship of religious interaction and national identity in the image of Vietnamese refugees in France and explores the ambivalence and ambiguity in their ideas about national identity.Received 29thDecember 2019; Revised 18thApril 2020; Accepted 20th April 2020